Testing Whether Suicide Capability Has a Dynamic Propensity: The Role of Affect and Arousal on Momentary Fluctuations in Suicide Capability - Law, Keyne C.; Anestis, Michael D. (Frontiers in Psychology, 2021)
To prevent suicidal behaviors, it is crucial to understand the mechanisms and processes that enable an individual to act on suicidal thoughts. Suicide capability, which involves an increased pain tolerance and fearlessness of death, is a critical factor that enables an individual to endure the physical pain necessary to make a lethal suicide attempt (Joiner, 2005; Klonsky & May, 2015). Extant research has largely conceptualized suicide capability as developing linearly in response to painful and provocative experiences, but the emerging literature on the temporal dynamics of suicide has been challenging the notion of linearity in suicide risk. Few studies have directly measured and compared changes in suicide capability in response to rumination on different affective states. We sought to experimentally test if rumination in the context of low vs. high arousal emotions will prompt distinct changes in two core components of suicide capability: pain tolerance and fearlessness of death on two undergraduate student samples. In both studies, participants provided measures of subjective emotional state as well as pain threshold, tolerance, and persistence before and after completing experimental manipulations which included both emotion and rumination induction procedures. In the second study, measures of fearlessness about death and physiological arousal (heart rate) were added to the experimental procedures. We found significant decreases in pain threshold, tolerance, and persistence following the experimental manipulations but found no main effects of rumination or suicide risk. These findings suggest that suicide capability can fluctuate but these changes may occur through a different mechanism and/or differ between individuals at varying levels of suicide risk.